1986
DOI: 10.1099/0022-1317-67-10-2113
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphonuclear Leukocyte Dysfunction Associated with Feline Leukaemia Virus Infection

Abstract: SUMMARYThe chemiluminescent characteristics of enriched (>95%) peripheral blood polymorphonuclear leukocyte populations (PMN) from normal and feline leukaemia virus (FeLV)-infected cats were investigated. FeLV-infected cats demonstrated a significantly lower (P < 0.001) PMN chemiluminescent response when compared to the response of normal age-matched controls. Normal PMN treated with FeLVinfected cat serum exhibited a depressed response in comparison to control cells. A titration of serum from infected cats su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1987
1987
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…Decreased activation of neutrophils from FeLV experimentally infected animals during phagocytosis of serum-opsonized particles has been described previously (Lewis et al, 1986). Likewise, neutrophils from FeLV 2 animals were not activated by opsonized particles with serum obtained from FeLV + cats (Lewis et al, 1986).…”
Section: Net Release and Myeloperoxidase (Mpo) Activitymentioning
confidence: 88%
See 3 more Smart Citations
“…Decreased activation of neutrophils from FeLV experimentally infected animals during phagocytosis of serum-opsonized particles has been described previously (Lewis et al, 1986). Likewise, neutrophils from FeLV 2 animals were not activated by opsonized particles with serum obtained from FeLV + cats (Lewis et al, 1986).…”
Section: Net Release and Myeloperoxidase (Mpo) Activitymentioning
confidence: 88%
“…Previous studies have shown that FeLV infection impairs neutrophil microbicidal functions and that affected cats are more susceptible to opportunistic infections Lewis et al, 1986). Decreased activation of neutrophils from FeLV experimentally infected animals during phagocytosis of serum-opsonized particles has been described previously (Lewis et al, 1986).…”
Section: Net Release and Myeloperoxidase (Mpo) Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent reports have shown that infection with the human retrovirus, human immunodeficiency virus, results in suppression of mononuclear phagocytic cells (Prince et al, 1985) and polymorphonuclear phagocytic cells (Ras et al, 1984). Lewis et al (1986) have shown that, in addition to lymphoid cell suppression, FeLV-viraemic cats express severely depressed PMN 0000-7273 © 1987 SGM populations as compared to controls in an assay for functional capacity in vitro. In addition, we have shown ) that non-viraemic FeLV-challenged cats express a similar depression in functional activity in vitro.…”
Section: Introductionmentioning
confidence: 99%